Ensuring Reproductive Rights of Women in Nepal: Law and Praxis - Parajuli, D. N. (Researcher: A Research Journal of Culture and Society, 2020)
Reproductive rights are fundamental rights and freedoms relating to reproduction and reproductive health that vary amongst countries around the world, but have a commonality about the protection, preservation and promotion of a woman‘s reproductive health rights. Reproductive rights include the right to autonomy and self-determination , the right of everyone to make free and informed decisions and have full control over their body, sexuality, health, relationships, and if, when and with whom to partner, marry and have children , without any form of discrimination, stigma, coercion or violence. The access and availability of reproductive health services are limited due to geography and other issues, non-availability and refusal of reproductive health services may lead to serious consequences. The State need to ensure accessibility, availability, safe and quality reproductive health services and address the lifecycle needs of women and girls and provide access of every young women and girls to comprehensive sexuality education based on their evolving capacity as their human rights, through its inclusion and proper implementation in school curriculum, community-based awareness program and youth led mass media. It is necessary for strengthening compliance, in a time-bound manner, with international human rights standards that Nepal has ratified that protect, promote, and fulfill the basic human rights and reproductive health rights in Nepal and also need to review standards and conventions that Nepal has had reservations about or those that have been poorly implemented in the country.